Sarawak General Hospital main block building retrofit features for energy efficiency - Muhammad Syukri, Imran (Universiti Malaysia Sarawak, (UNIMAS), 2011)
The purpose of this study is to evaluate the energy use of the Sarawak General Hospital main medical block building and to propose a low energy measures that would satisfy the Malaysian Energy Standard MS1525 solar heat gain through building envelope (OTTV) maximum recommended value of 50W/m2. Cooling and lighting alone constitute about 56% of energy use in the building which if energy efficiency strategies were applied to could produce a significant energy savings. A few measures wee considered which included double low e glazing, shading devices such as overhangs and fins and high reflective coatings. The potential and limitation of the measures on the cooling load of the building were assessed with the use of building energy pogram Energy Plus.